Portal-mesenteric vein resection for pancreatic cancer: Results in par with the defined benchmark outcomes - Tsiotos, Gregory G.; Ballian, Nikiforos; Milas, Fotios; Ziogou, Panoraia; Papaioannou, Dimitrios; Salla, Charitini; Athanasiadis, Ilias; Stavridi, Flora; Strimpakos, Alexios; Psomas, Maria; Kostopanagiotou, Georgia (Frontiers in Surgery, 2023)
Background: Patients with pancreatic cancer (PC), which may involve major peripancreatic vessels, have been generally excluded from surgery, considering that resection in such a setting may be futile. We report on the largest Greek series of portomesenteric vein resection in borderline resectable or locally advanced PC. Materials and Methods: Retrospective analysis of prospectively collected data on patients with borderline resectable or locally advanced adenocarcinoma undergoing pancreatectomy en-block with portal and/or superior mesenteric vein resection in a tertiary referral center in Greece between January 2014 and October 2021. Follow-up was complete up to December 2021. Operative and outcome measures were determined. Results: Forty patients were included. Neoadjuvant therapy was administered to only 58% and was associated with smaller tumor size (median: 2.9cm vs 4.2cm, p=0.004), but not with survival. Venous wall infiltration was present in 55%, it was not associated with tumor size, or with Eastern Cooperative Oncology Group (ECOG) status. Resection was extensive: a median of 27 LNs were retrieved, R0 resection rate (>1mm) was 87%, and median length of resected vein segments was 3cm, requiring interposition grafts in 40% (polytetrafluoroethylene). Median ICU stay was 0 days and length of stay 9 days. Postoperative mortality was 2.5%. Median follow-up was 46 months and median overall survival was 24 months. Two-, 3- and 5-year OS rate was 49%, 33%, and 22% respectively. All outcomes exceeded benchmark cutoffs. ECOG status was significantly associated with survival (ECOG-0: 32 months, ECOG-1: 24 months, ECOG-2: 12 months, p=0.02). Conclusion: This series of portomesenteric resection in borderline resectable or locally advanced PC demonstrated a median survival of 2 years, extending to 32 months in patients with good performance status, while exceeding outcome benchmarks.